Chromatin-directed proteomics identifies ZNF84 as a p53-independent regulator of p21 in genotoxic stress response - Strzeszewska-Potyrała, Anna; Staniak, Karolina; Czarnecka-Herok, Joanna; Rafiee, Mahmoud-Reza; Herok, Marcin; Mosieniak, Grażyna; Krijgsveld, Jeroen; Sikora, Ewa (Cancers, 2021)
The p21WAF1/Cip1 protein, encoded by CDKN1A, plays a vital role in senescence, and its transcriptional control by the tumour suppressor p53 is well-established. However, p21 can also be regulated in a p53-independent manner, by mechanisms that still remain less understood. We aimed to expand the knowledge about p53-independent senescence by looking for novel players involved in CDKN1A regulation. We used a chromatin-directed proteomic approach and identified ZNF84 as a novel regulator of p21 in various p53-deficient cell lines treated with cytostatic dose of doxorubicin. Knock-down of ZNF84, an as-yet un-characterized protein, inhibited p21 gene and protein expression in response to doxorubicin, it attenuated senescence and was associated with enhanced proliferation, indicating that ZNF84-deficiency can favor senescence bypass. ZNF84 deficiency was also associated with transcriptomic changes in genes governing various cancer-relevant processes e.g., mitosis. In cells with ZNF84 knock-down we discovered significantly lower level of H2AX Ser139 phosphorylation (γH2AX), which is triggered by DNA double strand breaks. Intriguingly, we observed a reverse correlation between the level of ZNF84 expression and survival rate of colon cancer patients. In conclusion, ZNF84, whose function was previously not recognized, was identified here as a critical p53-independent regulator of senescence, opening possibilities for its targeting in novel therapies of p53-null cancers.